AKTIVITAS ANTIBAKTERI JUS DAUN SIRIH (Piper bettle linn) TERHADAP BAKTERI PATOGEN DAN KUALITAS TELUR SELAMA PENYIMPANAN - Nining Haryuni; Eko Widodo; Edhy Sudjarwo (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2015)
Antibacterial activity of Piper bettle linn juice on pathogenic bacteria and its effect on egg quality during storage were studied. The method used in this study was experiment arranged in Completely Randomized Design. The Piper bettle linn juice was tested for their antibacterial activities against Escherichia coli, Salmonella sp and lactic acid bacteria in in vitro experiment. All of tested bacteria were challenged by different levels of Piper bettle linn juice dilution namely 0%, 25%, 50%, 75% and 100%. Increased Piper bettle linn juice level very significant affected (P<0,01). Growth inhibition of all tested bacteria was shown in diameter of inhibition zone (mm). The effects of Piper bettle linn juice were also tested on storage time legth of egg. Two hundred fifty 69-week-old Isa Brown layers were received different levels of 0%; 2,5%; 5%; 7,5%; 10% and 12,5% of Piper bettle linn juice added to the basal feed. The treatment has no effect on Salmonella total plate count of eggs but it very significant affected (P<0,01) egg quality especially on Escherichia coli total plate count and length of storage time. Key word : antibacterial activity, Piper bettle linn juice, pathogen bacteria, egg quality,storage time